Jeffrey E. B Rower. Aquinas’s ontology of the material world. Change, hylomorphism and material objects . Oxford University Press, Oxford, 2014, ISBN: 978-0-19-871429-3, 327+22 pp. - Cuccia, Emiliano Javier (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Centro de Estudios Filosóficos Medievales., 2016)

(untitled)
Fil: Cuccia, Emiliano Javier.